Reference intervals for peripheral blood natural killer cell, monocyte, and dendritic cell subsets in healthy adults from Zhejiang province, China - Longyi Zhang; Xuya Chen; Rui Xing; Yan Lu (BMC Immunology)
Abstract Background Given that immune cell profiles vary by region, age, and ethnicity, no standardized reference ranges currently exist for the proportions and absolute counts of natural killer (NK) cell, monocyte, and dendritic cell (DC) subsets in peripheral blood samples. This study aimed to establish age-stratified reference intervals for these immune cell subsets in healthy adults from Zhejiang Province, China. ​Methods This study enrolled healthy individuals aged 18–65 years who underwent routine health examinations at the Affiliated Dongyang Hospital of Wenzhou Medical University between April 2023 and October 2024. NK cells were categorized into CD56high, CD56+CD16+, and CD56+CD16− subsets. Monocyte populations were classified as classical monocytes (Mo1; CD14⁺CD16⁻), intermediate monocytes (Mo2; CD14⁺CD16⁺), and non-classical monocytes (Mo3; CD14dimCD16⁺). DCs were differentiated into plasmacytoid DCs (pDCs; CD123+) and myeloid DCs (mDCs; CD11c+). A dual-platform detection system was employed to comprehensively analyze the proportions and absolute counts of NK cell, monocyte, and DC subsets in peripheral blood samples. Nonparametric percentile methods (P2.5–P97.5) were applied to establish reference intervals, with subsequent validation performed in an independent cohort of 40 volunteers. Results​​ 316 healthy volunteers were enrolled to establish the reference intervals, comprising 155 participants in the 18–40 year age range (79 men and 76 women) and 161 in the 41–65 year group (77 men and 84 women). Age-stratified reference intervals were successfully established for NK cell, monocyte, and DC subsets. Validation showed ≥ 95% conformity rates. Age was positively correlated with NK cell proportions and Mo3 subsets (proportions and counts, p < 0.05) and negatively correlated with pDC/mDC absolute counts and Mo1/DC subsets (proportions and counts, p < 0.05). Notably, sex does not significantly modulate age-related changes in the dynamics of NK cell, monocyte, and DC subsets (all interaction terms p > 0.05). Conclusions This study provides age-stratified reference intervals for peripheral blood NK cell, monocyte, and DC subsets in Zhejiang adults, validated in an independent cohort. Sex does not influence age-related dynamics. These intervals offer critical clinical benchmarks for diagnosing and managing diseases involving immune cell dysregulation.